Effect of surfactant concentration on the spreading properties of pesticide droplets on Eucalyptus leaves. (March 2016) - Lin, Huan; Zhou, Hongping; Xu, Linyun; Zhu, Heping; Huang, Huanhua
Abstract : The area wetted by 500-μm diameter droplets of pesticide and deionised water placed at different positions on Eucalyptus urophylla × E. grandis (E.u × E.g) and Eucalyptus tereticornis (E.t) leaves was determined at an air temperature of 30 °C and a relative humidity of 60%. Dimethyl dichlorovinyl phosphate (DDVP), and efficient cypermethrin (EC) were diluted 1000 times in deionised water. Solutions the pesticides were prepared with surfactant concentrations (SC) of 0.1%, 0.25%, 0.5%, and 1%. For comparison SC solutions with water and deionised water were also used. Droplet deposition positions were located in the interveinal area, midrib, and secondary vein on both adaxial and abaxial surfaces. Without surfactant, all droplets remained nearly spherical and did not spread on the leaf surfaces. With surfactant, the deionised water and pesticide droplets had distinct spreading properties. For deionised water, both the wetted area and spread effectiveness peaked at 0.1% SC, while for pesticide droplets the wetted area peaked at 1% SC. However, the optimum SC was 0.25%. Compared with droplets on E.u × E.g leaves, droplets spread more on E.t leaves. The adaxial surface had better wettability than the abaxial surface. For pesticide droplets, the wetted area was a minimum on the midrib and the wetted area on the secondary vein was slightly larger than that on the interveinal area. Graphical abstract: Highlights: Deionised water and diluted pesticide droplets were deposited on Eucalyptus leaves. Surfactant was added to the spray solutions and different concentrations. Deionised water and pesticide droplets have different spreading properties. Specific spray solutions had optimal spreading at a specific surfactant concentration.